Sc-Fe-Zn-O superlattice nanoparticles as well as preparation method and application thereof

By wrapping ZnO nanoparticles with Sc-Fe-Zn-O precursor and using Joule heat technology, the problems of high energy consumption and low control accuracy of preparation of ZnO superlattice nanoparticles in the prior art are solved, and efficient and uniform Superglass nanoparticles and are used to make sensors with good gas-sensitive properties, enabling accurate monitoring in industrial and chemical experiments.

CN119191362APending Publication Date: 2024-12-27SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326316.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, long preheating time, insufficient temperature control, difficulty in adapting to large-size samples, limited control accuracy, and uneven temperature distribution of nanoparticles in the preparation of ZnO superlattice nanoparticles. .

Method used

The Sc-Fe-Zn-O precursor is used to wrap ZnO nanoparticles and pass constant current and rapid heating Joule heat technology to replace the traditional tube furnace heat treatment to prepare superlattice with good dispersion, uniform composition and good crystallinity. Nanoparticles.

Benefits of technology

It realizes efficient preparation with simple process and easy to promote, is suitable for large-scale production, and improves the performance of nanoparticles and the comprehensive gas-sensitive performance of gas-sensitive sensors, and can accurately and quickly monitor environmental changes in industrial production and chemical experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191362A_ABST
    Figure CN119191362A_ABST
Patent Text Reader

Abstract

The invention discloses an Sc-Fe-Zn-O superlattice nanoparticle as well as a preparation method and application thereof, and belongs to the technical field of superlattice nanoparticle materials. On the basis of the characteristics of the material, a high-temperature solid-state diffusion technology is adopted, a Joule heat process is used for replacing a traditional tubular furnace heat treatment process, ZnO nano-particles wrapped with the Sc-Fe-Zn-O composite precursor are interacted and reconstructed under the assistance of the precursor, and finally the nano-particles with the superlattice structure are synthesized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of superlattice nanoparticle materials, and specifically relates to Sc-Fe-Zn-O superlattice nanoparticles and a preparation method and application thereof. Background Art

[0002] Hydrogen sulfide (H2S), a colorless and pungent toxic gas, exists in a wide range of fields, including industrial production processes, sewage treatment systems, daily operations of chemical laboratories, and natural gas extraction. High concentrations of hydrogen sulfide (H2S) are extremely harmful to human health, mainly affecting the eyes, respiratory tract, and nervous system. In view of the widespread presence of hydrogen sulfide (H2S) in many key areas and its potential hazards, the development of high-performance H2S gas sensors has become a top priority. These sensors need to have high sensitivity, excellent selectivity, low cost, and long-term stable operation capabilities to meet urgent needs in many aspects, from environmental protection, industrial production monitoring to human health protection.

[0003] With the rapid development of nanoscience, functional material design and sensor technology, a series of innovative research results have provided strong support for the breakthrough of H2S detection technology. The existing technology has successfully achieved the detection of higher concentration (20ppm) H2S at room temperature by doping Pd into SnO2-core / ZnO-shell nanorods. This achievement reduces energy consumption and operational complexity. In addition, the existing technology has also prepared a new sensor based on SnO2 (ZnO: Sn) m superlattice nanoparticles, which can detect ultra-low concentration (ppb level) H2S. This technological leap has opened up a new path for ultra-sensitive H2S detection.

[0004] In the current research on element doping to obtain ZnO superlattice nanomaterials, researchers mostly use conventional tube furnaces for heat treatment to obtain ZnO superlattice nanoparticles. Although the use of tube furnaces to prepare superlattice nanoparticles has the advantages of mature technology, easy operation, and easy control, it also has some significant disadvantages, mainly including: high energy consumption, long preheating time, insufficient temperature control, difficulty in adapting to large-sized samples, limited control accuracy, and the nucleation and growth of nanoparticles may be affected by uneven temperature distribution. These disadvantages limit the preparation efficiency and performance optimization of nanoparticles. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a Sc-Fe-Zn-O superlattice nanoparticle and a preparation method and application thereof, which solves the problems of high energy consumption, long preheating time, insufficiently steep temperature control, difficulty in adapting to large-size samples, limited control accuracy, and nucleation and growth of nanoparticles being affected by uneven temperature distribution in the prior art.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing Sc-Fe-Zn-O superlattice nanoparticles, comprising the following steps:

[0007] S1: dissolving scandium salt, iron salt and zinc salt in an organic solvent at an atomic ratio of Sc:Fe:Zn of 5:5:4, and adding a stabilizer to the organic solvent to obtain a mixed solution;

[0008] S2: The mixed solution is stirred uniformly at 60-80°C and 400-500 r / min, and aged at room temperature for 24 hours to obtain an organic precursor solution;

[0009] S3: adding nano zinc oxide particles into an organic solvent at a solid-liquid ratio of 1-2 g:9 mL, and subjecting the ZnO nanoparticles to a dispersion after ultrasonic crushing and degassing;

[0010] S4: mixing the organic precursor solution prepared in S2 and the ZnO nanoparticle dispersion prepared in S3 at a volume ratio of 1:1-2, subjecting the mixed solution to ultrasonic grinding, degassing treatment, and drying treatment to obtain a precursor powder;

[0011] S5: subjecting the precursor powder to Joule heat treatment to obtain Sc-Fe-Zn-O superlattice nanoparticles; the Joule heat treatment process is to place the precursor powder under a constant current condition of 16A and heat it for 25 to 125s.

[0012] The beneficial effects of the present invention are as follows: based on the concept of diffusion reaction, the present invention adopts a method of synthesizing superlattice nanoparticles by heat treating a Sc-Fe-Zn-O precursor to wrap ZnO nanoparticles, and adopts a constant current and rapid heating Joule heat technology to replace the traditional tube furnace heat treatment to prepare superlattice nanoparticles with good dispersibility, uniform composition and good crystallinity; the method has a simple process, is easy to promote, and has excellent industrial prospects.

[0013] Based on the above technical solution, the present invention can also be improved as follows.

[0014] Furthermore, the scandium salt is scandium nitrate, the iron salt is iron nitrate, and the zinc salt is zinc acetate.

[0015] Furthermore, the organic solvent in S1 and S3 is ethylene glycol methyl ether.

[0016] Furthermore, the stabilizer is ethanolamine.

[0017] The beneficial effect of adopting the further technical solution is that the raw materials are cheap and readily available, and are suitable for large-scale production.

[0018] Furthermore, the ultrasonic crushing process in S3 and S4 is to perform ultrasonic cleaning at a frequency of 50kHz to 1MHz for 15 minutes, and then ultrasonic crushing at a power of 55% for 7 seconds, with an interval of 1 second, and this operation is repeated for a total of 15 minutes.

[0019] Furthermore, the degassing process in S3 and S4 is stirring at a speed of 70 r / min for 15 min under vacuum conditions.

[0020] Furthermore, the drying process in S4 is drying at 150° C. for 40 minutes.

[0021] The beneficial effect of adopting a further technical solution is that the ZnO nanoparticles can be further refined and the coating of the precursor can be promoted, and finally superlattice nanoparticles with good dispersion, uniform composition and good crystallinity can be obtained.

[0022] The invention also discloses the Sc-Fe-Zn-O superlattice nanoparticles prepared by the preparation method of the Sc-Fe-Zn-O superlattice nanoparticles.

[0023] The invention also discloses the application of Sc-Fe-Zn-O superlattice nanoparticles in preparing gas sensitive sensor materials.

[0024] The beneficial effects of the present invention are as follows: the gas sensor made of Sc-Fe-Zn-O superlattice nanoparticles has good comprehensive gas-sensing performance, which is helpful for accurately and quickly monitoring and responding to environmental changes in industrial production, closed environments and chemical experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 (a) is a STEM image of the precursor powder of 100 nm size obtained in Example 1. Figure 1 (b) is a STEM image of the precursor powder of 50 nm size obtained in Example 1;

[0026] Figure 2 is a STEM image of Sc-Fe-Zn-O superlattice nanoparticles prepared in comparative example;

[0027] Figure 3 The STEM image of the superlattice layered structure of the Sc-Fe-Zn-O superlattice nanoparticles prepared in the comparative example;

[0028] Figure 4 This is a STEM image of the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 2;

[0029] Figure 5 This is a STEM image of the superlattice layered structure of the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 2;

[0030] Figure 6 This is a STEM image of the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1;

[0031] Figure 7 This is a STEM image of the superlattice layered structure of the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1;

[0032] Figure 8 XRD diagrams of Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and Comparative Example;

[0033] Fig. 9 The XRD patterns of the Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and Comparative Example at 30 to 40 degrees are magnified;

[0034] Fig.10 The XRD patterns of the Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and the comparative example at 40 to 70 degrees are shown;

[0035] Fig.11 The gas selectivity spectrum of the gas sensor prepared from the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1;

[0036] Fig.12 The response-recovery curve of the gas sensor prepared from the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1;

[0037] Fig.13 This is the repeatability curve of the gas sensor made from the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1;

[0038] Fig.14 The response-recovery curve of the gas sensor prepared from the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 2;

[0039] Fig.15 This is the repeatability curve of the gas sensor made from the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 2;

[0040] Fig.16 The response-recovery curve of the gas sensor prepared by the Sc-Fe-Zn-O superlattice nanoparticles prepared in the comparative example;

[0041] Fig.17 This is the repeatability curve of the gas sensor made of Sc-Fe-Zn-O superlattice nanoparticles obtained in the comparative example. DETAILED DESCRIPTION

[0042] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0043] Example 1

[0044] A method for preparing Sc-Fe-Zn-O superlattice nanoparticles comprises the following steps:

[0045] S1: Scandium nitrate, iron nitrate and zinc acetate were dissolved in 10 mL of ethylene glycol methyl ether solvent (the material-liquid ratio of solute to solvent was 1 mol:100 L) at an atomic ratio of Sc:Fe:Zn of 5:5:4, and then 6 μL of ethanolamine was added to the mixed solution to obtain a mixed solution;

[0046] S2: The mixed solution was stirred uniformly at 70°C and 450 r / min, and aged at room temperature for 36 h to obtain an organic precursor solution;

[0047] S3: 1.5 g of nano zinc oxide particles were added to 9 mL of ethylene glycol methyl ether solvent, and ultrasonically cleaned at a frequency of 75 kHz for 15 min, and then ultrasonically crushed at a power of 55% for 7 s with an interval of 1 s. This operation was repeated for a total of 15 min, and then the ultrasonically treated solution was transferred to a stirring degassing machine, and stirred at a speed of 70 r / min for 15 min under vacuum conditions to obtain a ZnO nanoparticle dispersion;

[0048] S4: The organic precursor solution prepared in S2 and the ZnO nanoparticle dispersion prepared in S3 were mixed in a volume ratio of 1:1.5, and ultrasonically cleaned at a frequency of 70kHz for 15 minutes, and then ultrasonically crushed at a power of 55% for 7 seconds with an interval of 1 second. This operation was repeated for a total of 15 minutes, and then the ultrasonically treated solution was transferred to a stirring degassing machine, and stirred at a speed of 70r / min for 15 minutes under vacuum conditions. Finally, the mixed solution was evenly spread on a quartz boat, and then the quartz boat was placed in a constant temperature drying oven set at a temperature of 150°C and dried for 40 minutes to obtain a precursor powder;

[0049] S5: Wrap the precursor powder with graphite paper and place it between carbon felts. Then, connect the circuit at both ends of the carbon felt, pass a constant current of 16A, and heat for 125s to obtain Sc-Fe-Zn-O superlattice nanoparticles.

[0050] Example 2

[0051] A method for preparing Sc-Fe-Zn-O superlattice nanoparticles comprises the following steps:

[0052] S1: Scandium nitrate, iron nitrate and zinc acetate were dissolved in 10 mL of ethylene glycol methyl ether solvent (the material-liquid ratio of solute to solvent was 1 mol:100 L) at an atomic ratio of Sc:Fe:Zn of 5:5:4, and then 6 μL of ethanolamine was added to the mixed solution to obtain a mixed solution;

[0053] S2: The mixed solution was stirred uniformly at 60°C and 500 r / min, and aged at room temperature for 24 h to obtain an organic precursor solution;

[0054] S3: 1 g of nano zinc oxide particles was added to 9 mL of ethylene glycol methyl ether solvent, and ultrasonic cleaning was performed at a frequency of 50 kHz for 15 min, and then ultrasonic crushing was performed at a power of 55% for 7 s, with an interval of 1 s, and this operation was repeated for a total of 15 min, and then the ultrasonically treated solution was transferred to a stirring degassing machine, and stirred at a speed of 70 r / min for 15 min under vacuum conditions to obtain a ZnO nanoparticle dispersion;

[0055] S4: The organic precursor solution prepared in S2 and the ZnO nanoparticle dispersion prepared in S3 were mixed in a volume ratio of 1:1, ultrasonically cleaned at a frequency of 75kHz for 15 minutes, and then ultrasonically crushed at a power of 55% for 7 seconds with an interval of 1 second. This operation was repeated for a total of 15 minutes, and then the ultrasonically treated solution was transferred to a stirring degassing machine, stirred at a speed of 70r / min for 15 minutes under vacuum conditions, and finally the mixed solution was evenly spread on a quartz boat. Subsequently, the quartz boat was placed in a constant temperature drying oven set at a temperature of 150°C and dried for 40 minutes to obtain a precursor powder;

[0056] S5: Wrap the precursor powder with graphite paper and place it between carbon felts. Then, connect the circuit at both ends of the carbon felt, pass a constant current of 16A, and heat for 25s to obtain Sc-Fe-Zn-O superlattice nanoparticles.

[0057] Comparative Example

[0058] A method for preparing Sc-Fe-Zn-O superlattice nanoparticles comprises the following steps:

[0059] S1: Scandium nitrate, iron nitrate and zinc acetate were dissolved in 10 mL of ethylene glycol methyl ether solvent (the material-liquid ratio of solute to solvent was 1 mol:100 L) at an atomic ratio of Sc:Fe:Zn of 5:5:4, and then 6 μL of ethanolamine was added to the mixed solution to obtain a mixed solution;

[0060] S2: The mixed solution was stirred uniformly at 80°C and 400 r / min, and then aged at room temperature for 48 hours to obtain an organic precursor solution;

[0061] S3: 2 g of nano zinc oxide particles were added to 9 mL of ethylene glycol methyl ether solvent, and ultrasonically cleaned at a frequency of 80 kHz for 15 min, and then ultrasonically crushed at a power of 55% for 7 s with an interval of 1 s. This operation was repeated for a total of 15 min, and then the ultrasonically treated solution was transferred to a stirring degassing machine, and stirred at a speed of 70 r / min for 15 min under vacuum conditions to obtain a ZnO nanoparticle dispersion;

[0062] S4: The organic precursor solution prepared in S2 and the ZnO nanoparticle dispersion prepared in S3 were mixed in a volume ratio of 1:2, and ultrasonically cleaned at a frequency of 75kHz for 15 minutes, and then ultrasonically crushed at a power of 55% for 7 seconds with an interval of 1 second. This operation was repeated for a total of 15 minutes, and then the ultrasonically treated solution was transferred to a stirring degassing machine, and stirred at a speed of 70r / min for 15 minutes under vacuum conditions. Finally, the mixed solution was evenly spread on a quartz boat, and then the quartz boat was placed in a constant temperature drying oven set at a temperature of 150°C and dried for 40 minutes to obtain a precursor powder;

[0063] S5: Wrap the precursor powder with graphite paper and place it in a tube furnace. Set the annealing temperature to 900°C for 30 min to obtain Sc-Fe-Zn-O superlattice nanoparticles.

[0064] Experimental Example 1

[0065] Characterization experiment 1: Scanning transmission electron microscopy (STEM) was used to scan the precursor powder prepared in Example 1. The results are as follows: Figure 1 As shown in the figure, the ZnO nanoparticles are tightly wrapped by a uniform layer of precursor colloid, which leads to a certain aggregation state between the nanoparticles due to colloid adhesion. Despite the aggregation, the size of the individual particles remains within the range of about 30nm, further confirming the uniformity of the precursor coating and the size stability of the nanoparticles.

[0066] Experimental Example 2

[0067] Characterization Experiment 2: Scanning transmission electron microscopy (STEM) was used to scan the Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and the comparative example. Figures 2 to 7As shown, the particle size range of the Sc-Fe-Zn-O superlattice nanoparticles (comparative example) obtained by tubular furnace annealing extends to between 60 and 70 nm, and the inner edges of some nanoparticles begin to show layered structures (clearly marked with blue arrows). These layered structures are stacked in an orderly manner along the axial direction of the nanoparticles, confirming that these layered structures are superlattice structures in the formation stage, but the formation of the superlattice structure is not yet complete and only appears in some areas. The particle size of the Sc-Fe-Zn-O superlattice nanoparticles obtained in Example 2 is further increased to 70 to 90 nm, and the contrast of the light and dark contrast on the surface becomes more distinct, which directly reflects the more complex and orderly changes in the internal structure. This phenomenon strongly proves that the Joule heat treatment effectively promotes the mutual diffusion and fusion of Sc, Fe, and Zn elements between the ZnO nanoparticle matrix and the Sc-Fe-Zn-O precursor. At this time, the superlattice layered structure not only increases in number, but also runs through the entire nanoparticle, showing a clearly discernible and highly ordered arrangement. This change indicates that the formation of superlattice structure has entered a more mature stage. The Joule heat treatment time of Example 1 reached 125s, and the particle size of the nanoparticles reached a new height of about 115nm. At the same time, the layered structure completely and regularly penetrated the entire nanoparticle, forming a typical superlattice nanoparticle. This achievement not only verifies the powerful ability of Joule heat treatment in regulating nanostructures, but also demonstrates the possibility of optimizing the performance of nanomaterials by precisely controlling heating conditions.

[0068] Experimental Example 3

[0069] Characterization Experiment 3: The Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and the comparative example were scanned using an X-ray diffractometer. The results are as follows: Figures 8 to 10 As shown, the Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and the comparative example are dominated by hexagonal wurtzite ZnO, and the characteristic diffraction peaks such as (100), (002) and (101) are clearly discernible, and there is no interference from impurities, indicating that the dominant position of ZnO is stable and there is no deflection of the preferred orientation. It is particularly noteworthy that compared with the matrix ZnO nanoparticles, the diffraction peaks of the Sc-Fe-Zn-O superlattice nanoparticles show sharper contours and enhanced intensity, which is not only direct evidence of its particle size growth, but also indicates better crystallization performance. With the increase of the heating time of the Joule heating technology, the half-peak width of the diffraction peak gradually narrows, and the peak shape becomes sharper, which clearly indicates the growth trend of the nanoparticle size.

[0070] Further focus on Fig. 9 and Fig.10From the fine spectra in the range of 30-40° and 40-70°, it can be clearly observed that the (002) and (101) diffraction peaks of the Sc-Fe-Zn-O superlattice nanoparticles have undergone slight shifts. This subtle but critical change is the direct proof that the two elements Sc and Fe have been successfully doped and penetrated into the lattice, causing the adjustment of the lattice parameters; it not only verifies the effectiveness of element doping, but also deeply reveals the positive role of lattice distortion in the formation of superlattice structure. In summary, the detailed analysis of the XRD spectrum reveals the exquisite structural evolution process of Sc-Fe-Zn-O superlattice nanoparticles under Joule heat treatment.

[0071] Experimental Example 4

[0072] Gas-sensitive selectivity experiment: Under a constant working temperature of 300°C, a variety of representative gases including H2, CO, NH3, NO2, CH4 and H2S were selected, and the concentration of each gas was set to 100 ppm to simulate the gas environment that may be encountered in actual applications. The Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1 were used as raw materials to prepare gas sensors for testing. The test results are shown in FIG. Fig.11 As shown in the figure, when the sensor is exposed to 100ppm H2S, its response value (expressed as Ig / Ia) is as high as 65, showing an extremely sensitive response characteristic. In contrast, for other test gases with the same concentration, the sensor's responsivity is maintained at a level close to 1, which can almost be regarded as a non-responsive state. This sharp contrast strongly proves that the sensor has extremely high selectivity and recognition ability for H2S gas, and exhibits good anti-interference and stability when facing other interfering gases.

[0073] Experimental Example 5

[0074] Gas-sensitive response-recovery and repeatability experiment: A gas-sensitive sensor was prepared under a constant operating temperature of 300°C and a H2S gas concentration of 100 ppm using the Sc-Fe-Zn-O superlattice nanoparticles prepared in Examples 1 to 2 and the comparative example as raw materials for testing. The test results are shown in FIG. Figures 12 to 17 As shown, the responsivity of the gas sensor prepared using the Sc-Fe-Zn-O superlattice nanoparticles prepared in the comparative example as raw materials is 9, the responsivity of the gas sensor prepared using the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 2 as raw materials is increased to 28.7, and the responsivity of the gas sensor prepared using the Sc-Fe-Zn-O superlattice nanoparticles prepared in Example 1 as raw materials reaches 253, and it only takes 8 seconds from the injection of H2S to the peak response.

[0075] In summary, the present invention is based on the concept of diffusion reaction, adopts a method of synthesizing superlattice nanoparticles by heat treatment of Sc-Fe-Zn-O precursor wrapped ZnO nanoparticles, and adopts constant current and rapid heating Joule heat technology to replace the traditional tube furnace heat treatment to prepare superlattice nanoparticles with good dispersibility, uniform composition and good crystallinity. And a gas sensor based on Sc-Fe-Zn-O superlattice nanoparticles is made, which obtains good comprehensive gas sensing performance, which is helpful to accurately and quickly monitor and respond to environmental changes in industrial production, closed environments and chemical experiments.

[0076] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing Sc-Fe-Zn-O superlattice nanoparticles, characterized in that: The following steps are involved: S1: dissolving scandium salt, iron salt and zinc salt in an organic solvent at an atomic ratio of Sc:Fe:Zn of 5:5:4, and adding a stabilizer to the organic solvent to obtain a mixed solution; S2: stirring the mixed solution at 60-80°C at a speed of 400-500 r / min, and aging at room temperature for 24-48 hours to obtain an organic precursor solution; S3: adding nano zinc oxide particles into an organic solvent at a solid-liquid ratio of 1-2 g:9 mL, and subjecting the mixture to ultrasonic grinding and degassing to obtain a ZnO nanoparticle dispersion; S4: mixing the organic precursor solution prepared in S2 and the ZnO nanoparticle dispersion prepared in S3 at a volume ratio of 1:1-2, subjecting the mixed solution to ultrasonic grinding, degassing treatment, and drying treatment to obtain a precursor powder; S5: subjecting the precursor powder to Joule heat treatment to obtain Sc-Fe-Zn-O superlattice nanoparticles; the Joule heat treatment process is to place the precursor powder under a constant current condition of 16A and heat it for 25 to 125s.

2. The method for preparing Sc-Fe-Zn-O superlattice nanoparticles according to claim 1, characterized in that: The scandium salt is scandium nitrate, the iron salt is iron nitrate, and the zinc salt is zinc acetate.

3. The method for preparing Sc-Fe-Zn-O superlattice nanoparticles according to claim 1, characterized in that: The organic solvent in S1 and S3 is ethylene glycol methyl ether.

4. The method for preparing Sc-Fe-Zn-O superlattice nanoparticles according to claim 1, characterized in that: The stabilizer is ethanolamine.

5. The method for preparing Sc-Fe-Zn-O superlattice nanoparticles according to claim 1, characterized in that: The ultrasonic crushing process in S3 and S4 is to ultrasonically clean at a frequency of 50kHz to 80kHz for 15 minutes, and then ultrasonically crush at a power of 55% for 7 seconds, with an interval of 1 second, and repeat this operation for a total of 15 minutes.

6. The method for preparing Sc-Fe-Zn-O superlattice nanoparticles according to claim 1, characterized in that: The degassing process in S3 and S4 is to stir at a speed of 70 r / min for 15 min under vacuum conditions.

7. The method for preparing Sc-Fe-Zn-O superlattice nanoparticles according to claim 1, characterized in that: The drying process in S4 is drying at 150° C. for 40 minutes.

8. Sc-Fe-Zn-O superlattice nanoparticles obtained by the preparation method of Sc-Fe-Zn-O superlattice nanoparticles according to any one of claims 1 to 7.

9. Use of the Sc-Fe-Zn-O superlattice nanoparticles according to claim 8 in the preparation of gas sensors.

10. The use according to claim 9, characterized in that: The gas sensor is a sensor for detecting H2S.